Correlation of Surface Cracks of Concrete due to Corrosion and Bond Strength (between Steel Bar and Concrete) - Charis Alk. Apostolopoulos; Konstantinos F. Koulouris; Alkiviadis Ch. Apostolopoulos (Advances in Civil Engineering)
The current experimental study presents the results of bond strength loss (steel bar concrete) due to the corrosion damage of steel bar specimens, semiembedded in concrete, at various times of exposure to corrosive environment. In this case, a correlation was made between the width of the surface cracks of concrete caused by reinforcing steel corrosion and bond strength for different distances between stirrups and different cover thickness of concrete. The study indicates close relationship between the width of surface cracking, the percentage mass loss of embedded reinforcing bar, the distance between stirrups, and the cover thickness. In addition, mathematical predictive models of bond strength loss of corroded specimens were proposed. The model outcomes showed that the cracking development on concrete surface up to a width of 1.6 mm is accompanied by an exponential reduction of bond strength loss between steel reinforcement and concrete. Furthermore, the investigation has shown that the increase of transverse reinforcement (stirrups) percentage and the cover thickness play a significant role in durability of reinforced concrete elements and in bond strength maintenance between rebar and concrete.